Thermal maturation and exhumation of a middle orogenic crust in the Livradois area (French Massif central) - Gardien, V.; Vanderhaeghe, O.; Arnaud, N.; Cocherie, A.; Grange, Marion; Lecuyer, C. (2011)
Upper Carboniferous heating and melting of the middle orogenic crust associated with the emplacement of syntectonic granitoids are documented in the Upper Gneissic Unit of the Livradois area (central part of the French Massif Central). Crustal melting post-dates peak metamorphism conditions (800-625°C, 10-8 kb) dated at 360 ± 4 Ma (U-Th-Pb on monazite). The P-T evolution of the metamorphic series indicates that Barrovian metamorphism was followed by a decompression (from 10 ± 1 kbar to 6 ± 1 kbar) associated with either a decrease in temperature in the southern part of the series or with an increase in temperature (of about 150°C) in the northern part of the series. This evolution records the first step of the exhumation of the series coeval with granitoids intrusion, of which the emplacements were dated at 315 ± 4 and 311 ± 18 Ma (U-Pb on zircon). The final stage of the exhumation is associated with an isobaric cooling of the whole series. Similarity of 40Ar/39Ar ages for biotite in the paragneisses (307-300 Ma) and K-feldspar in the granitoids (306-300 Ma) document rapid cooling for this stage. Moreover dextral reverse mylonites, at the border and the northern part of the metamorphic series indicate north-south compression coeval with the unroofing of the series. Youngest 40Ar-39Ar ages on K-feldspar (274.6 ± 5 Ma) combined with normal shearing in mylonites limiting the Carboniferous Brassac-les-Mines basin document the late Carboniferous-early Permian stage of extension coeval with the upwelling of the Velay granitic dome.